Application of a topical collagen agent after tooth extraction to control hemostasis should be immediate and not delayed: a comparative randomized trial - Protin Anaïs; Cameli Charlotte; Sérandour Anne-Laure; Hamon Julien; Chaux Anne-Gaëlle; Guillemin Maxime; Thibaut Flora (EDP Sciences, 2023)
Objective: The main objective was to demonstrate that the delay of placement of a collagen-based hemostatic cylindrical dressing, here ETIK COLLAGENE, affects postoperative bleeding. Other objectives were to evaluate the safety of this medical device. Material and methods: 38 patients under antithrombotic treatment and consulting for tooth extraction were included. The antithrombotic treatment was maintained. Patients were randomized: In group 1: the hemostatic dressing ETIK COLLAGENE was applied immediately after the tooth extraction and curettage; the surgeon assessed the presence of bleeding (Yes/No) every 30 s up to a total time of 8 min, then he sutured. In group 2: the bleeding was assessed every 30 s up to a total time of 8 min immediately after the tooth extraction and curettage, then the surgeon placed ETIK COLLAGENE before suturing. Seven days later, patients were asked about the occurrence of bleedings and adverse events. Results: The mean bleeding time after tooth extraction was of 1:13 ± 0:49 (min: sec) and 3:39 ± 3:06 respectively in the group 1 and in the group 2; the difference between groups is 2:26 (95% CI [0:52 - 4:01]) in favor to the group 1 (p = 0.0144). There were significantly more adverse effects in group 2. Conclusions: The delay in placement of ETIK COLLAGENE after extraction has an impact on bleeding time and postoperative adverse events: these parameters are reduced in a statistically significant way when the placement is performed immediately after the end of the curettage rather than after an 8 min delay.